Trastuzumab-induced corneal ulceration: successful no-drug treatment of a "blind" side effect in a case report. Issue 1 (December 2015) - Orlandi, A.; Fasciani, R.; Cassano, A.; Agresta, A.; Calegari, M.; Caporossi, A.; Barone, C.
Abstract Background We report the first successful treatment of limbal lesions and corneal erosion experienced by a breast cancer patient undergoing trastuzumab treatment. Case presentation A 49-year-old Caucasian woman with early stage breast cancer was treated with adjuvant trastuzumab and subsequently showed persistent bilateral corneal marginal infiltrates resistant to topical steroid and antibiotic treatment. Autologous serum was applied in the conjunctival sac as an experimental treatment to antagonize the inhibitory effect of the HER2 receptor antibody on the corneal epithelial cells. Topical application of autologous serum led to rapid improvement of the ulcerative keratitis, with complete healing of the corneal defect after 7 days. Continued administration of the serum allowed the resumption of trastuzumab therapy without any further side effects. Conclusions Persistent bilateral corneal marginal infiltrates may occasionally arise as a side effect of trastuzumab treatment. Topical medication with autologous serum may be an effective therapeutic option for the ocular side effects of trastuzumab therapy.